Análise e Previsão Adaptativa de Vendas na Indústria: Uma Abordagem de Negócio Inteligente - Ramos, Rui Jorge Soares (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics